2002
DOI: 10.4049/jimmunol.168.11.5722
|View full text |Cite
|
Sign up to set email alerts
|

Matrix Fibronectin Increases HIV Stability and Infectivity

Abstract: HIV particles are detected extracellularly in lymphoid tissues, a major reservoir of the virus. We previously reported that a polymerized form of fibronectin (FN), superfibronectin (sFN), as well as a fragment of FN, III1-C, enhanced infection of primary CD4+ T cells by HIV-1IIIB. We now show that sFN enhances infection of primary CD4+ T cells by both R5 and X4 strains of HIV-1. Using HIV pseudotyped with different envelope glycoproteins (gp120) and HOS cells transfected with various chemokine receptors alone … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
35
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(37 citation statements)
references
References 35 publications
2
35
0
Order By: Relevance
“…Recent reports suggest that diverse forms of matrix FN can stabilize virions of HIV-1 on the surface of infected cells and help facilitate the transmission of infectious virus (24,25). We have also found that addition of FNf to cultures of in vitro infected MNLs stimulated with IL-2 increases by 2-to 4-fold the quantity of p24 generated over the next 3 days (data not shown).…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…Recent reports suggest that diverse forms of matrix FN can stabilize virions of HIV-1 on the surface of infected cells and help facilitate the transmission of infectious virus (24,25). We have also found that addition of FNf to cultures of in vitro infected MNLs stimulated with IL-2 increases by 2-to 4-fold the quantity of p24 generated over the next 3 days (data not shown).…”
Section: Discussionsupporting
confidence: 52%
“…Recent studies have called attention to the possibility that proteolytic fragments or polymers of FN may be among the factors that influence leukocyte behavior in inflamed tissues (23)(24)(25). Certain FN fragments can stabilize and enhance the infectivity of cell-associated virus (24,25); other FN subunits can activate monocytes and cause them to release TNF-␣ through a protein kinase C-dependent signaling pathway (26 -30).…”
Section: Impact Of Fibronectin Fragments On the Transendothelial Migrmentioning
confidence: 99%
See 1 more Smart Citation
“…We previously reported that HIV virions adhered efficiently to superfibronectin, an in vitro model for matrix fibronectin (3). Superfibronectin-bound virions had enhanced infectivity and maintained their infectivity significantly longer than unbound virions (2). Additionally, proteolytic fragments of fibronectin containing the III1-C region also enhanced HIV infection.…”
mentioning
confidence: 89%
“…We previously showed that fibronectin deposition was increased in lymph nodes during HIV infection but did not find a difference in fibronectin synthesis by HIV-infected lymphocytes (2). Therefore, we hypothesized that interactions of HIV-infected lymphocytes with fibroblasts would result in increased fibronectin synthesis by fibroblasts.…”
Section: Increased Fibronectin Depositionmentioning
confidence: 99%